207k views
3 votes
- 2y + 3 = - 4y
The solution set is what???

2 Answers

7 votes
You would add -2y to -4y and get -6y then you would divide -6 and 3 and you would get 3/-6= -0.5 so. Y=-0.5 I hope this helped
User Priscella
by
4.8k points
0 votes

Answer:

Y=-3/2

Explanation:

-2y+3=-4y

Move constant to the right by adding its opposite to both sides

-2y+3-3=-4y-3

Eliminate the opposites

-2y=-4y-3

collect the like terms

-2y+4y

collect the like terms

(-2+4)y

Calculate the sum

2y=-3

divide both sides of the equation by 2

2y÷2=-3÷2

Any expression divided by itself equal 1

y=-3÷2

y=-3/2

User Keshav M
by
4.2k points